Hyperbaric oxygen therapy as an immunosensitizing strategy in advanced gastric hepatoid adenocarcinoma: a case report - Li, Wenke; Wei, Jing; Zhang, Pengfei; Cheng, Mo; Xu, Menghui; Zhu, Lin; Liu, Ming (Frontiers in Immunology, 2025)
BackgroundHepatoid adenocarcinoma of the stomach (HAS) is a rare but highly aggressive subtype of gastric cancer (GC) associated with an unfavorable prognosis, particularly in advanced or metastatic stages. While the standard first-line treatment for advanced GC involves immune checkpoint inhibitors (ICIs) combined with chemotherapy, HAS often shows a poor therapeutic response to this regimen. The hypoxia in the tumor microenvironment is considered a key factor limiting ICI efficacy, and combining hyperbaric oxygen therapy (HBOT) with immunotherapy may offer a synergistic sensitizing effect.MethodsWe report a case of advanced HAS with peritoneal metastasis who received standard first-line immunochemotherapy (CAPOX plus sintilimab). After four cycles, the patient achieved only stable disease (SD) per RECIST 1.1 criteria. Consequently, HBOT was introduced as a sensitizing agent after the fifth cycle, and the patient subsequently completed the sixth cycle. This report was prepared using the CARE reporting guideline and checklist (Supplement A).ResultsFollowing the addition of HBOT, the patient’s tumor markers normalized. Subsequent imaging and endoscopic evaluations revealed a complete resolution of all lesions, meeting the criteria for a clinical complete response (cCR) under RECIST 1.1.ConclusionsThis case suggests that adding HBOT may enhance the efficacy of immunotherapy and overcome resistance to ICIs in advanced HAS. These promising findings warrant further investigation through prospective clinical studies to confirm this observation.